Catalytic ink for forming electrode catalyst layer and method for manufacturing membrane electrode assembly

JP7652081B2Active Publication Date: 2025-03-27TOPPAN HOLDINGS INC
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021563858
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-09
Filing Date
2020-11-27
Publication Date
2025-03-27
Estimated Expiration
2040-11-27

AI Technical Summary

Benefits of technology

【0008】 本発明の態様に係る触媒インクを用いることにより、炭素繊維や有機電解質繊維の絡み合いにより、膜強度が高まり、触媒インクを直接、電解質膜に塗布した際においても、しわやひび割れを抑制することが出来る。更に、本発明の態様に係る触媒インクを用いることにより、炭素繊維が電子導電性を付与し、有機電解質繊維がプロトン導電性を付与することで、性能の低下を抑制することが出来る。 この結果、本発明の態様によれば、膜電極接合体の製造時に、直接高分子電解質膜に触媒インクを塗布した際においても、発電性能を低下させることなく、触媒層のしわやひび割れを抑制することが可能となる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007652081000001
    Figure 0007652081000001
  • Figure 0007652081000002
    Figure 0007652081000002
  • Figure 0007652081000003
    Figure 0007652081000003
Patent Text Reader

Abstract

Provided are: a catalyst ink that can be directly applied on a polyelectrolyte membrane without causing crimps or cracks, or without diminishing performance; and a membrane electrode assembly using said catalyst ink. This catalyst ink for use in forming an electrode catalyst layer contains, in a solvent, a polyelectrolyte and catalyst-carrying carbon particles on which a catalyst is carried, and contains carbon fibers and / or organic electrolyte fibers. The catalyst ink has a particle grain-size distribution in which peaks are present within a range of 0.1-1 μm and a range of 1-10 μm. Said catalyst ink is applied directly on a polyelectrolyte membrane (9) to produce a membrane electrode assembly.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a catalyst ink for forming an electrode catalyst layer of a polymer electrolyte fuel cell, and a method for producing a membrane electrode assembly using the catalyst ink. [Background technology]

[0002] A polymer electrolyte fuel cell has a structure in which a polymer electrolyte membrane is sandwiched between a cathode electrode catalyst layer and an anode electrode catalyst layer. Because polymer electrolyte fuel cells with such a structure operate at room temperature and have a short start-up time, they are expected to be used as a power source for automobiles and stationary power sources. Known conventional methods for producing a membrane electrode assembly include a method in which a catalyst ink is directly applied to a polymer electrolyte membrane, and a method in which a catalyst ink is applied to a transfer substrate or a gas diffusion layer, and then the substrate or layer is thermocompressed to the polymer electrolyte membrane. The catalyst ink is, for example, composed of carbon particles carrying a catalyst, a polymer electrolyte, and a solvent.

[0003] Among these, the method of producing a membrane electrode assembly by directly applying a catalyst ink to a polymer electrolyte membrane has the characteristics of good adhesion at the interface between the polymer electrolyte membrane and the electrode catalyst layer and of not crushing the catalyst layer by thermocompression bonding, and therefore this method of producing a membrane electrode assembly can produce a membrane electrode assembly with excellent power generation performance and durability. However, in conventional manufacturing methods in which catalyst ink is directly applied to an electrolyte membrane, the solvent in the ink causes the polymer electrolyte membrane to swell or shrink when the catalyst ink is applied, which creates the problem of making the formed catalyst layer prone to wrinkles and cracks.

[0004] To address the above-mentioned problems, in Patent Document 1, a needle-shaped carbon material such as carbon nanotubes is used for the electrode catalyst layer, making it possible to form the catalyst layer directly on the electrolyte membrane. However, this method has the potential of reducing power generation performance due to low catalyst utilization, and furthermore, needle-shaped carbon materials such as carbon nanotubes are bulky and entanglement of the needle-shaped carbon materials can make the catalyst ink highly viscous, making it difficult to apply. On the other hand, in Patent Document 2, the performance is improved by preparing an electrode catalyst layer formed mainly of a fibrous proton conductive material. However, although this method improves performance, it may not be possible to obtain a membrane strength sufficient to suppress wrinkles and cracks in the catalyst layer when directly applied to the electrolyte membrane. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2002 / 027844 [Patent Document 2] JP 2007-220416 A Summary of the Invention [Problem to be solved by the invention]

[0006] The present invention has been made in view of the above-mentioned points, and has an object to provide a catalyst ink that can be directly applied to a polymer electrolyte membrane without causing wrinkles or cracks and without deteriorating performance, and a membrane electrode assembly using the catalyst ink. [Means for solving the problem]

[0007] In order to solve the above problems, a catalyst ink for an electrode catalyst layer according to one embodiment of the present invention comprises, in a solvent, catalyst-supported carbon particles, which are carbon particles supporting a catalyst, and a polymer electrolyte, and also comprises at least one of carbon fibers and organic electrolyte fibers, and has a particle size distribution having peaks in the ranges of at least 0.1 μm to 1 μm and 1 μm to 10 μm, respectively. Another aspect of the present invention is a method for producing a membrane electrode assembly by directly applying a catalyst ink to a polymer electrolyte membrane, the method comprising the steps of: (a) applying a catalyst ink to a polymer electrolyte membrane; and (b) applying a catalyst ink to an electrode catalyst layer having the above-described structure as the catalyst ink. Effect of the Invention

[0008] By using the catalyst ink according to the embodiment of the present invention, the carbon fibers and the organic electrolyte fibers are entangled to increase the membrane strength, and wrinkles and cracks can be suppressed even when the catalyst ink is directly applied to the electrolyte membrane. Furthermore, by using the catalyst ink according to the embodiment of the present invention, the carbon fibers impart electronic conductivity and the organic electrolyte fibers impart proton conductivity, thereby suppressing deterioration of performance. As a result, according to this aspect of the present invention, even when a catalyst ink is applied directly to a polymer electrolyte membrane during the production of a membrane electrode assembly, it is possible to suppress wrinkles and cracks in the catalyst layer without reducing power generation performance. [Brief description of the drawings]

[0009] [Figure 1] 1 is an exploded perspective view showing the internal structure of a polymer electrolyte fuel cell according to one embodiment of the present invention; [Diagram 2] 1 is a diagram illustrating a structure of a membrane electrode assembly for a polymer electrolyte fuel cell according to one embodiment of the present invention. [Diagram 3] FIG. 4 is a diagram showing the measurement results of particle size distribution of a catalyst ink according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. Note that this embodiment is not limited to the embodiment described below, and modifications such as design changes based on the knowledge of those skilled in the art are possible, and embodiments with such modifications are also included in the scope of this embodiment. Moreover, in the following detailed description, specific details are set forth in order to provide a thorough understanding of the embodiments of the present invention. However, it will be apparent that one or more embodiments may be practiced without such specific details. In addition, for the sake of clarity in the drawings, well-known structures and devices may be shown in simplified form.

[0011] (Structure of polymer electrolyte fuel cells) 1, a pair of electrode catalyst layers 3A, 3F are arranged on both sides of a polymer electrolyte membrane 2 constituting a solid polymer fuel cell 1, facing each other with the polymer electrolyte membrane 2 sandwiched between them. A gas diffusion layer 4A is arranged on the surface of the electrode catalyst layer 3A opposite to the surface facing the polymer electrolyte membrane 2, and a gas diffusion layer 4F is arranged on the surface of the electrode catalyst layer 3F opposite to the surface facing the polymer electrolyte membrane 2, so as to face each other with the polymer electrolyte membrane 2 and the pair of electrode catalyst layers 3A, 3F sandwiched between them.

[0012] On the surface of the gas diffusion layer 4A opposite to the surface facing the electrode catalyst layer 3A, a separator 5A is disposed, the separator 5A having a gas flow passage 6A for flowing a reactant gas on the main surface facing the gas flow passage 6A and a cooling water passage 7A for flowing cooling water on the main surface opposite to the main surface having the gas flow passage 6A. Furthermore, on the surface of the gas diffusion layer 4F opposite to the surface facing the electrode catalyst layer 3F, a separator 5F is disposed, the separator 5F having a gas flow passage 6F for flowing a reactant gas on the main surface facing the gas flow passage 6A and a cooling water passage 7F for flowing cooling water on the main surface opposite to the main surface having the gas flow passage 6F. Hereinafter, when there is no need to distinguish between them, the electrode catalyst layers 3A and 3F may be simply referred to as "electrode catalyst layer 3".

[0013] Fig. 2 is a schematic cross-sectional view showing an example of the configuration of an electrode catalyst layer according to this embodiment. As shown in Fig. 2, an electrode catalyst layer 8 according to this embodiment is bonded to the surface of a polymer electrolyte membrane 9. The electrode catalyst layer 8 is composed of a catalyst 10, carbon particles 11 as a conductive support, a polymer electrolyte 12 and carbon fibers 13, and organic electrolyte fibers 14. The portions where none of the components of the catalyst 10, the carbon particles 11, the polymer electrolyte 12 and carbon fibers 13, or the organic electrolyte fibers 14 are present are voids.

[0014] (Catalyst ink manufacturing) Next, a method for producing the catalyst ink for forming an electrode catalyst layer according to this embodiment will be described. The catalyst ink for forming an electrode catalyst layer is used to form the electrode catalyst layers 3 and 8 (electrode catalyst layers for a polymer electrolyte fuel cell) of the polymer electrolyte fuel cell 1. First, the carbon particles 11 constituting the catalyst-supported carbon particles supporting the catalyst 10, and the polymer electrolyte 12 are mixed and dispersed in a dispersion medium (solvent) to obtain a catalyst particle slurry. For example, metals and alloys, oxides, double oxides, carbides, etc. of these metals can be used as the catalyst 10. Examples of metals include platinum group elements (platinum, palladium, ruthenium, iridium, rhodium, osmium), iron, lead, copper, chromium, cobalt, nickel, manganese, vanadium, molybdenum, gallium, aluminum, etc.

[0015] Any material may be used as the carbon particles 11 as long as it is conductive and capable of supporting the catalyst without being corroded by the catalyst, but carbon particles are generally used. As the dispersion medium (solvent), any one of water and alcohols such as methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, isobutyl alcohol, tert-butyl alcohol, pentanol, etc. may be selected and used. In addition, as the dispersion medium, a dispersion medium in which two or more of the above-mentioned dispersion media are mixed may be used. For example, a bead mill, a planetary mixer, a dissolver, etc. may be used for mixing and dispersion.

[0016] Materials for the polymer electrolyte membranes 2, 9 and the polymer electrolyte 12 may be any materials having proton conductivity, and may include fluorine-based polymer electrolytes and hydrocarbon-based polymer electrolytes. As the fluorine-based polymer electrolyte, a polymer electrolyte having a tetrafluoroethylene skeleton may be used. For example, "Nafion (registered trademark)" manufactured by DuPont may be used. The polymer electrolyte 12 is in a state where the polymer electrolyte is aggregated. Next, at least one of the carbon fibers 13 and the organic electrolyte fibers 14 is added to the catalyst particle slurry produced by the above method, and mixed and dispersed to obtain a catalyst ink. For example, a bead mill, a planetary mixer, a dissolver, etc. can be used for mixing and dispersing.

[0017] Examples of the carbon fiber 13 include carbon fiber, carbon nanotube, carbon nanohorn, conductive polymer nanofiber, etc. Only one type of these fibers may be used alone, or two or more types may be used in combination. The polymer electrolyte 12 and the polymer electrolyte constituting the organic electrolyte fibers 14 may be the same material or different from each other. Furthermore, the polymer electrolytes constituting the polymer electrolyte 12 and the organic electrolyte fibers 14, and the polymer electrolytes constituting the polymer electrolyte membranes 2 and 9 may be the same material or different from each other.

[0018] (Manufacturing of membrane electrode assemblies) The electrode catalyst layers 3 formed from the above-mentioned catalyst ink are bonded to both sides of the polymer electrolyte membrane 2 to produce a membrane electrode assembly. As a method for bonding the electrode catalyst layer 3 to the polymer electrolyte membrane 2, for example, a transfer substrate with an electrode catalyst layer, which is formed by applying a catalyst ink to a transfer substrate, is used, and the surface of the electrode catalyst layer of the transfer substrate with the electrode catalyst layer is brought into contact with the polymer electrolyte membrane, followed by heating and pressurization, thereby bonding the polymer electrolyte membrane 2 and the electrode catalyst layer 3.

[0019] However, the above method results in poor adhesion between the electrode catalyst layer 3 and the polymer electrolyte membrane 2, and voids are likely to form at the interface between the electrode catalyst layer 3 and the polymer electrolyte membrane 2. This tends to lead to problems such as a decrease in power generation performance due to interface resistance and a decrease in power generation performance due to flooding caused by water clogging the voids. On the other hand, a membrane electrode assembly can also be produced by a method in which a catalyst ink is directly applied to the surface of the polymer electrolyte membrane 2, and then the solvent component (dispersion medium) is removed from the coating of the catalyst ink. This method provides good adhesion between the electrode catalyst layer 3 and the polymer electrolyte membrane 2, making the above-mentioned problems less likely to occur.

[0020] However, in the method of directly applying the catalyst ink to the polymer electrolyte membrane 2, there has traditionally been a problem in that the applied electrode catalyst layer 3 is prone to wrinkles and cracks due to swelling of the polymer electrolyte membrane 2, which can easily lead to reduced power generation performance and reduced durability. In contrast, if at least one of the carbon fibers 13 and the organic electrolyte fibers 14 is added to the catalyst ink as in this embodiment, the strength of the electrode catalyst layer 3 is increased. Specifically, a catalyst ink consisting only of catalyst-supporting carbon particles having a particle size in the range of 0.1 μm to 1 μm is prone to aggregation due to the small size of the catalyst-supporting carbon particles, and wrinkles and cracks are likely to occur in the applied electrode catalyst layer 3. Therefore, in this embodiment, by adding the above-mentioned fibers 13 having a particle size in the range of 1 μm to 10 μm, aggregation of the catalyst-supporting carbon particles having a small particle size can be suppressed, and wrinkles and cracks are suppressed in the applied electrode catalyst layer 3.

[0021] In this case, if the peak in the particle size distribution in the catalyst ink in the range of 0.1 μm or more and 1 μm or less falls outside the range of 0.1 μm or more and 1 μm or less, aggregation cannot be suppressed completely, and wrinkles and cracks are likely to occur in the applied electrode catalyst layer 3. Furthermore, if the particle size distribution in the catalyst ink has a peak in the range of 1 μm or more and 10 μm or less, when the ink is applied to form a thin coating, the unevenness will become significant, which may cause damage to the polymer electrolyte membrane 2. On the other hand, in a catalyst ink consisting only of large particles with diameters in the range of 1 μm to 10 μm, the specific surface area of ​​the catalyst is insufficient, resulting in reduced catalytic activity and causing a decrease in performance.

[0022] In addition, when the viscosity of the catalyst ink is high, the coating and drying process becomes difficult, and wrinkles and cracks are likely to occur in the electrode catalyst layer 3 during the coating and drying process. Specifically, when the thixotropic index (TI value) between the viscosity at a shear rate of 10 (1 / s) and the viscosity at a shear rate of 100 (1 / s) exceeds 10, coating becomes difficult and wrinkles and cracks are likely to occur. A catalyst ink consisting of only small particle diameters is prone to particle aggregation, resulting in a high TI value. On the other hand, a catalyst ink consisting of small particles showing a peak value of the particle size distribution in the range of 0.1 μm to 1 μm and large particles showing a peak value of the particle size distribution in the range of 1 μm to 10 μm suppresses aggregation, so it does not become high viscosity and is less likely to cause wrinkles and cracks when applied to the electrode catalyst layer 3.

[0023] Here, in the catalyst ink of this embodiment, as described above, the catalyst-supporting carbon particles form a peak value of the particle size distribution in the range of 0.1 μm to 1 μm, and the added fibers form a peak value of the particle size distribution in the range of 1 μm to 10 μm. The formation of each of the above peak values ​​is possible, for example, if the particle diameters of the target particles are within the respective corresponding ranges at 60% wt or more, and preferably 80 wt or more. If the solids concentration of the catalyst ink is higher than 20 wt %, the viscosity will increase and it will be difficult to apply a thin film, making it more likely to cause wrinkles and cracks when applied to the electrode catalyst layer 3.

[0024] On the other hand, when the viscosity of the catalyst ink is low, specifically when the thixotropic index (TI value) of the viscosity at a shear rate of 10 (1 / s) and the viscosity at a shear rate of 100 (1 / s) is less than 1.5, the catalyst ink is prone to wrinkles and cracks during the drying process when applied to the electrode catalyst layer 3. The average fiber diameter of the organic electrolyte fibers 14 is 2 μm or less. If the average fiber diameter is 2 μm or less, the fiber material is ensured to be appropriately fine as to be contained in the electrode catalyst layer. In order to improve the output of a polymer electrolyte fuel cell, it is desirable that the gas supplied to the electrode catalyst layer is appropriately diffused into the electrode catalyst layer through the pores in the electrode catalyst layer, and that water generated by the electrode reaction, particularly at the air electrode, is appropriately discharged through the pores. In addition, the presence of pores makes it easier to form an interface where the gas, catalyst-supporting carbon, and polymer electrolyte come into contact, promoting the electrode reaction, which also makes it possible to improve the output of the polymer electrolyte fuel cell.

[0025] From the above viewpoints, it is preferable that the electrode catalyst layer has pores of an appropriate size and amount. If the average fiber diameter of the organic electrolyte fibers 14 is 2 μm or less, sufficient gaps are formed in the structure in which the organic electrolyte fibers 14 are entangled in the electrode catalyst layer, and sufficient pores are secured, so that the output of the fuel cell can be improved. Furthermore, if the average fiber diameter of the organic electrolyte fibers 14 is 0.5 nm or more and 500 nm or less, the output of the fuel cell is particularly increased. The average fiber length of the organic electrolyte fibers 14 is preferably greater than the average fiber diameter and is 1 μm or more and 200 μm or less. When the average fiber length is within the above range, aggregation of the organic electrolyte fibers 14 in the electrode catalyst layer is suppressed, and pores are easily formed. Furthermore, when the average fiber length is within the above range, an entangled structure of the organic electrolyte fibers 14 is suitably formed in the electrode catalyst layer, thereby increasing the strength of the electrode catalyst layer and improving the effect of suppressing the occurrence of cracks.

[0026] (Effects of this embodiment) According to the present embodiment, even when a catalyst ink is directly applied to a polymer electrolyte membrane during the manufacture of a membrane electrode assembly, it is possible to suppress wrinkles and cracks in the catalyst layer without deteriorating the power generation performance, which makes it possible to manufacture a membrane electrode assembly with good power generation performance without reducing the yield.

[0027] Examples and comparative examples of the present invention will be described below. (Example 1) Hereinafter, Example 1 of the present invention will be described. (Production of Catalyst Ink) Water was added to catalyst-supported carbon particles supporting 50 wt% of platinum (trade name: TEC10E50E, manufactured by Tanaka Kikinzoku Kogyo K.K.) and a dispersion of a polymer electrolyte (trade name: Nafion dispersion, manufactured by Wako Pure Chemical Industries, Ltd.), and they were mixed with a planetary mixer to prepare a catalyst particle slurry. Carbon fiber (trade name: VGCF-H, manufactured by Showa Denko) and 1-propanol were added to the above catalyst particle slurry, adjusted so that the solid content concentration became 10 wt%, and dispersed with a bead mill disperser to obtain a catalyst ink. The measurement result of the particle size distribution of the above catalyst ink was as shown in FIG. 3. That is, the catalyst ink of Example 1 was a catalyst ink having a particle size distribution having peaks in the range of 0.1 μm to 1 μm and in the range of 1 μm to 10 μm, respectively. Further, as a result of measuring the TI value of the viscosity at a shear rate of 10 (1 / s) and the viscosity at a shear rate of 100 (1 / s) of the catalyst ink of Example 1, it was 6.0.

[0028] <Measurement of Particle Size Distribution> Here, in this specification, the measurement of the particle size distribution in the catalyst ink was performed by the laser diffraction / scattering method. The measurement conditions are as follows. Measurement Conditions: Sample permeability: Absorption Solvent refractive index: 1.333

[0029] <Measurement of Shear Rate> In this specification, the measurement of the shear rate (viscosity measurement method) was performed under the following conditions. Measurement Conditions: Measuring device: Cone-plate viscometer Measurement range (shear rate): 1000 [1 / s] to 1 [1 / s] Measurement temperature: 23°C

[0030] <TI Value> The TI value is the ratio of viscosities. The TI value in this specification is defined as follows. TI value = Viscosity at shear rate of 10 [1 / sec] / Viscosity at shear rate of 100 [1 / sec]

[0031] (Manufacturing of membrane electrode assemblies) Next, the above catalyst ink was directly applied to both sides of the polymer electrolyte membrane by a die coating method to obtain a membrane electrode assembly. When the catalyst ink of Example 1 was applied directly to both sides of a polymer electrolyte membrane, no wrinkles or cracks were formed in the catalyst layer, and good power generation performance was obtained.

[0032] Example 2 Next, a second embodiment of the present invention will be described. The catalyst ink of Example 2 was obtained by the same process as in Example 1, except that polymer electrolyte fibers were added to the catalyst ink instead of carbon fibers. The polymer electrolyte fibers were produced by forming a polymer electrolyte dispersion (Nafion dispersion: manufactured by Wako Pure Chemical Industries, Ltd.) into fibers using the electrospinning method, followed by cooling and pulverization. The average fiber diameter of the polymer electrolyte fibers was 150 nm, and the average fiber length was 10 μm. The particle size distribution of the catalyst ink of Example 2 showed two peaks in the ranges of 0.1 μm to 1 μm and 1 μm to 10 μm. The catalyst ink of Example 2 had a TI value of 7.5 when the viscosity was measured at a shear rate of 10 (1 / s) and at a shear rate of 100 (1 / s). When the catalyst ink of Example 2 was applied directly to both sides of a polymer electrolyte membrane, no wrinkles or cracks were formed in the catalyst layer, and good power generation performance was obtained.

[0033] Example 3 Next, a third embodiment of the present invention will be described. The catalyst ink of Example 3 was obtained by the same process as in Example 1, except that after the carbon fiber of Example 1 was added, the same polymer electrolyte fiber as in Example 2 was added. The particle size distribution of the catalyst ink of Example 3 showed peaks in the range of 0.1 μm to 1 μm and in the range of 1 μm to 10 μm. The catalyst ink of Example 3 had a TI value of 4.5 when the viscosity was measured at a shear rate of 10 (1 / s) and at a shear rate of 100 (1 / s). When the catalyst ink of Example 3 was applied directly to both sides of a polymer electrolyte membrane, no wrinkles or cracks were formed in the catalyst layer, and good power generation performance was obtained.

[0034] Comparative Example 1 The catalyst ink of Comparative Example 1 was obtained by the same process as in Example 1 above, except that no carbon fiber was added to the catalyst ink. The particle size distribution of the catalyst ink of Comparative Example 1 showed one peak in the range of 0.1 μm to 1 μm. The TI value of the viscosity of the catalyst ink of Comparative Example 1 at a shear rate of 10 (1 / s) and at a shear rate of 100 (1 / s) was measured and found to be 11.0. When the catalyst ink of Comparative Example 1 was applied directly to both sides of a polymer electrolyte membrane, it resulted in the generation of wrinkles and cracks in the catalyst layer.

[0035] Comparative Example 2 The catalyst ink of Comparative Example 2 was obtained by the same process as in Example 1, except that the catalyst ink was produced so that the solid content concentration was 5 wt %. The particle size distribution of the catalyst ink of Comparative Example 2 showed two peaks, one in the range of 0.1 μm to 1 μm and the other in the range of 1 μm to 10 μm. The TI value of the viscosity of the catalyst ink of Comparative Example 2 at a shear rate of 10 (1 / s) and at a shear rate of 100 (1 / s) was measured and found to be 1.0. When the catalyst ink of Comparative Example 2 was applied directly to both sides of a polymer electrolyte membrane, it resulted in wrinkles and cracks in the catalyst layer.

[0036] Comparative Example 3 A catalyst ink of Comparative Example 2 was obtained by the same process as in Example 2, except that polymer electrolyte fibers with an average fiber diameter of 3.0 μm and an average fiber length of 20 μm were used as the organic electrolyte fibers. The particle size distribution of the catalyst ink of Comparative Example 3 showed two peaks, one in the range of 0.1 μm to 1 μm and the other in the range of 1 μm to 10 μm. The TI value of the viscosity of the catalyst ink at a shear rate of 10 (1 / s) and at a shear rate of 100 (1 / s) was measured and found to be 6.0. When the catalyst ink of Comparative Example 3 was applied directly to both sides of a polymer electrolyte membrane, no wrinkles or cracks were formed in the catalyst layer, but a slight decrease in power generation performance occurred.

[0037] Moreover, the scope of the present invention is not limited to the exemplary embodiments shown and described, but includes all embodiments that achieve the same effect as the object of the present invention. Moreover, the scope of the present invention is not limited to the combination of the features of the invention defined by the claims, but may be defined by any desired combination of specific features among all the respective features disclosed. In addition, the entire contents of Japanese Patent Application No. 2019-222431 (filed December 9, 2019), from which this application claims priority, are incorporated by reference into this disclosure. [Explanation of symbols]

[0038] 1 Polymer electrolyte fuel cell 2, 9 Polymer electrolyte membrane 3, 8 Electrode catalyst layer 3A, 3F Electrode catalyst layer 10. Catalyst 11 Carbon particles 12 Polyelectrolyte 13 Carbon Fiber 14 Organic electrolyte fiber

Claims

1. The catalyst-supporting carbon particles, which are carbon particles supporting a catalyst, and a polymer electrolyte are contained in a solvent, and at least one fiber selected from carbon fibers and organic electrolyte fibers is also contained, The particle size distribution has peaks in the range of at least 0.1 μm to 1 μm and in the range of at least 1 μm to 10 μm, A catalyst ink for forming an electrode catalyst layer, the catalyst ink having a solid content concentration of 8 wt % or more and 20 wt % or less, and a thixotropic index (TI value) of the viscosity at a shear rate of 10 (1 / s) and the viscosity at a shear rate of 100 (1 / s) of 1.5 or more and 10 or less.

2. 2. The catalyst ink for forming an electrode catalyst layer according to claim 1, wherein the carbon fibers contain one or more types selected from the group consisting of carbon nanofibers and carbon nanotubes.

3. 3. The catalyst ink for forming an electrode catalyst layer according to claim 1, wherein the organic electrolyte fibers have an average fiber diameter of 2 μm or less and an average fiber length of 1 μm or more and 200 μm or less.

4. A membrane electrode assembly using the catalyst ink for forming an electrode catalyst layer according to any one of claims 1 to 3.

5. A method for producing a membrane electrode assembly by directly applying a catalyst ink to a polymer electrolyte membrane, comprising the steps of: A method for producing a membrane electrode assembly, comprising the step of: using the catalyst ink for forming an electrode catalyst layer according to any one of claims 1 to 3 as the catalyst ink.

Citation Information

Patent Citations

  • Electrode constituent raw material for high-molecular solid electrolyte type fuel cell and manufacture thereof

    JP1996227716A

  • Electrode and power-generating layer for fuel cell, and manufacture of the same

    JP1998241703A

  • Electrode for fuel cell and method of manufacturing electrode for fuel cell

    JP2007220416A

  • Membrane electrode structure for fuel cell, and method of manufacturing the same

    JP2011165362A

  • Fuel cell, catalyst ink, and method for manufacturing catalyst ink

    JP2013168309A